P.46: Enhanced Single Viewing Zone Integral Imaging Display Based on Medium Packing Technique. Issue 1 (1st July 2013) - Luo, Cheng‐Gao; Wang, Qiong‐Hua
Abstract: Generally, the performances of integral imaging (II) are mainly limited by the narrow viewing zone and image flipping between different viewing zones. In this paper, an enhanced single viewing zone integral imaging display is proposed. Experiments are carried out and good results finally verify the feasibility of the proposed method.